The Amazons of the Apu Sara-Sara: «Qasiri warmi llaqta» (woman of people without husband) - Arroyo Aguilar, Sabino (2014)
Qasiri is a peasant community knowed as women village, because of the early emigration of the husbands in search of work, at the first decades of XX century; although, according to the oral version it would be a result of the underlyng history tradition of the ayllus andinos of precolombian origin.